Convexity subarachnoid hemorrhage: clinical features and etiology of an Argentinian cohort - Aníbal Chertcoff; Lucrecia Bandeo; Fátima Pantiu; Luciana León Cejas; Sol Pacha; Claudia Uribe Roca; Manuel Fernández Pardal; Ricardo Reisin; Pablo Bonardo (Arquivos de Neuro-Psiquiatria)
ABSTRACT Nontraumatic convexity subarachnoid hemorrhage is an increasingly recognized subtype of subarachnoid bleeding. Objective: Our aim was to describe the etiology and clinical features of a cohort of patients with convexity subarachnoid hemorrhage. Methods: We retrospectively analyzed all cases of convexity subarachnoid hemorrhage admitted to our hospital between January 2012 and April 2017. Demographic features, clinical characteristics, complementary investigations, etiology and mortality were assessed. Twenty patients (65% females) were identified. Mean age: 53 years (range, 15-86 years). Results: Symptoms on admission: headache (65%), sensory and/or motor symptoms (50%) and seizures (35%). Commonest causes: cerebral vein thrombosis (20%), reversible cerebral vasoconstriction syndrome (20%) and cerebral amyloid angiopathy (20%). Two patients died. Conclusion: Convexity subarachnoid hemorrhage may be related to a wide spectrum of etiologies. In our patients, an increased prevalence of cerebral vein thrombosis was observed. Mortality was low and not related to the bleeding itself.